Decentralized Model Predictive Control of Nonlinear System Using Piesewise LTI Model - Pham, Van Hung; Hoang, Minh Son (Old Journal, 2017)
This paper proposes a Decentralized Model Predictive Control (DMPC) schema for nonlinear systems consisting of a number of interconnected nonlinear subsystems. Each subsystem is controlled by a model predictive controller using piecewise Linear Time Invariant (LTI) predictive model and the predictive information from other model predictive controllers to predict disturbance and to calculate the optimal control signals with considering the effect of interconnections as perturbation term. Besides, the input-to-state stability (ISS) property of the local subsystems and the global system is guaranteed by some predetermined assumptions. The simulation results on the boiler-turbine system have demonstrated the performance of the proposed approach.